Synthesis, characterization and in vitro evaluation of novel enantiomerically-pure sulphonamide antimalarials. Issue 43 (8th September 2015) - Anusha, Sebastian; Sinha, Ameya; Babu Rajeev, C. P.; Chu, Trang T. T.; Mathai, Jessin; Ximei, Huang; Fuchs, Julian E.; Shivananju, NanjundaSwamy; Bender, Andreas; Preiser, Peter Rainer; Rangappa, Kanchugarakoppal S.; Basappa,; et al.
Abstract : Novel sulphonamide antimalarials targeting parasitic N -myristoyl transferase. Abstract : Malaria parasites are currently gaining drug-resistance rapidly, across countries and continents. Hence, the discovery and development of novel chemical scaffolds, with superior antimalarial activity remain an important priority, for the developing world. Our report describes the development, characterization and evaluation of novel bepotastine-based sulphonamide antimalarials inhibiting asexual stage development of Plasmodium falciparum parasites in vitro . The screening results showed potent inhibitory activity of a number of novel sulphonamides against P. falciparum at low micromolar concentrations, in particular in late-stage parasite development. Based on computational studies we hypothesize N -myristoyltransferase as the target of the compounds developed here. Our results demonstrate the value of novel bepotastine-based sulphonamide compounds for targeting the asexual developmental stages of P. falciparum .